The expression of HLA class I molecules and complement regulatory proteins in ovarian cancer - Rolland, Philip (2008)
Over recent decades, translational ovarian cancer research has been impeded by its underappreciated molecular heterogeneity and five-year survival has remained poor. One strategy for addressing this problem is to search for molecular biomarkers that can better inform the development and targeting of novel treatments. The aim of this thesis was to construct and validate a tissue microarray of ovarian cancer cases and to survey the expression and prognostic capabilities of immunological molecular markers: specifically HLA class I and the membrane bound complement regulatory proteins CD46, CD55 and CD59. These are central to the efficacy of certain immunotherapies and while they have been shown to have prognostic power in breast and colorectal cancer, they have been investigated less in ovarian cancer.